Crustal structures of Grenville, Makkovik, and southern Nain provinces along the Lithoprobe ECSOOT Transect: regional seismic refraction and gravity models and their tectonic implications - Louden, Keith E; Fan, Jianming (Canadian Journal of Earth Sciences, 1998)
Crustal structures of the eastern Grenville, Makkovik, and southern Nain provinces are determined using seismic reflection-refraction and gravity data along the Lithoprobe Eastern Canadian Shield Onshore-Offshore Transect (ECSOOT). Within the Grenville Province, the velocity model contains a 5 km thick upper crust and a variable-thickness middle to lower crust. The total crustal thickness varies from 25 to 43 km, with the thickest crust in the south and thinnest crust in the north. A high-velocity, lower crustal wedge is coincident with a strong band of northward-dipping reflectors. The two-dimensional velocity structure is compatible with modelling of a 60 mGal gravity high over the Hawke River terrane. In the Makkovik Province, the thickness of upper crustal velocities increases to 17 km. The velocity decrease in the upper to middle crust from the Grenville Province to the Makkovik Province is similar to that of refraction models across the Grenville Front in Ontario and Quebec. It is possibly related to a decrease in metamorphic grade from south to north and (or) a larger volume of unmetamorphosed plutons in the Makkovik Province. A lower crustal layer is coincident with a region of increased reflectivity in the lower crust. There are no major crustal discontinuities associated with terrane boundaries within the Makkovik Province. The base of the crust is consistent with a change from north- to south-dipping reflectors beneath the Cape Harrison domain. Alternatively, it may consist of a thick zone of complex velocity variations, consistent with a zone of diffusive reflectivity observed to the north of the Allik domain.